2002
DOI: 10.1016/s0924-9338(02)00682-x
|View full text |Cite
|
Sign up to set email alerts
|

Life events and changes in the course of depression in young adults

Abstract: The association between life events and the course of depression appears to vary according to the outcome being examined, with different clusters of life events differentially predicting onset, improvement, and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 43 publications
3
60
0
2
Order By: Relevance
“…18,19 These environmental conditions represent uncontrollable stressors, which have been hypothesized to undermine health more than controllable stressors. 8 If, as other work suggests, study respondents lived in their general neighborhoods for most of their pregnancy, 2 they may have become inured to the adverse environmental conditions to which they were regularly exposed. Therefore, finding even modest associations between neighborhood conditions and psychosocial health is meaningful.…”
Section: Discussionmentioning
confidence: 98%
“…18,19 These environmental conditions represent uncontrollable stressors, which have been hypothesized to undermine health more than controllable stressors. 8 If, as other work suggests, study respondents lived in their general neighborhoods for most of their pregnancy, 2 they may have become inured to the adverse environmental conditions to which they were regularly exposed. Therefore, finding even modest associations between neighborhood conditions and psychosocial health is meaningful.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, past studies have also revealed the significant relationship between adulthood emotional disorders and childhood abuse and neglect, maltreatment, and other traumatic experiences (Middeldorp, Cath, Dyck and Boomsma, 2005). Another study reported a positive relationship between childhood traumatic experiences and subsequent problems like anxiety and depression (Friis, Wittchen, Pfister and Lieb, 2002); somatization (Güleç et al, 2012); eating disorders, substance abuse and alcoholism (Yargıç, Tutkun and Şar, 2012); and dissociative disorders, borderline personality disorder, and conversion disorder (Şar, Akyüz, Kundakçı, Kızıliziltan, and Doğan, 2004). In another study, the authors revealed that exposure to emotional and sexual abuse by many people during childhood increases the risk of developing depression in adulthood (Liu, Jager-Hyman, Wagner, Alloy, and Gibb, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Friis e cols. 26 , em uma pesquisa longitudinal com uma amostra comunitária de adolescentes e adultos jovens de 14 a 24 anos, encontraram os eventos negativos de vida e o suporte familiar como preditores do desencadeamen-Refere-se ao Art. de mesmo nome, 14(3), [58][59][60][61][62][63][64][65][66][67]2004 to de novos episódios de depressão.…”
Section: Discussionunclassified